Implementation of Fast-Track Pediatric Surgery in a German Nonacademic Institution without Previous Fast-Track Experience - Schukfeh, Nagoud; Reismann, Marc; Ludwikowski, Barbara; Hofmann, Alejandro Daniel; Kaemmerer, Andrea; Metzelder, Martin L.; Ure, Benno (European Journal of Pediatric Surgery, 2014)
Fast-track concepts in pediatric surgery were established in a university hospital in consecutive studies within several years. They significantly reduced the length of hospitalization compared with German institutions without fast-track protocols. The aim of this study was to assess the implementation process of fast-track in a German nonacademic department of pediatric surgery without previous fast-track experience. All patients undergoing four types of operations (appendectomy, hypospadias repair, pyloromyotomy, and fundoplication) from February 2011 to January 2012 were included in this prospective study. Fast-track included detailed clinical pathways and specific pain treatment protocols using validated pain scales according to age. Mobilization and oral nutrition were started 2 hours postoperatively and documented with established scores. The length of hospital stay was compared with data from other hospitals with conventional treatment using information from the German reimbursement system (German diagnosis-related groups [G-DRG]) and with the hospital stay of patients from the corresponding university hospital undergoing fast-track treatment for the same procedures during the same study period. Two weeks after discharge, a questionnaire was completed by the patients/parents. A total of 143 patients with a mean age of 7.9 ± 5.0 years underwent fast-track treatment. The mean pain intensity during the immediate postoperative period was 1.7 ± 2.1 in patients < 4 years and 2.3 ± 2.1 in patients ≥ 4 years on a 10-point scale. Full mobilization was reached after a mean duration of 2.3 ± 2.0 days while full oral nutrition was completed after a mean duration of 1.8 ± 1.4 days. There were no complications associated with fast-track. The mean hospital stay was 5.8 ± 3.4 days which was not significantly different compared with G-DRG data from other hospitals without fast-track. This was in contrast to the mean hospital stay of patients from the corresponding university hospital (5.6 ± 3.0 days vs. G-DRG 6.9 ± 3.2 days, p < 0.05). After 2 weeks, patients/parents were highly satisfied with fast-track (mean score of 8.6 ± 1.4 on a 1–10-point scale) and 95.2% claimed that they would choose it again. Fast-track concepts can be applied in a nonacademic department of pediatric surgery without previous fast-track experience and with excellent patient/parent satisfaction. However, the G-DRG system interferes with concepts of early discharge of patients. Modifications of the reimbursement modalities within the German health care system seem to be mandatory.
Keywords: minimally invasive surgery; appendectomy; hypospadia; pyloric stenosis; fundoplication